Chemicals for War and Chemicals for Peace: Poison Gas in Bhopal, India, and Halabja, Kurdistan, Iraq - Sinha, Indra (Social justice, 2014)
The article focuses on the use of chemicals throughout history. Topics include the 1984 Union Carbide pesticide plant disaster that occurred in Bhopal, India, the use of social justice advertising by that nonprofit group Amnesty International, the use of chemical weapons on Halabja, Kurdistan by the Iraqi Army in 1988.